2021
DOI: 10.1038/s41598-021-95728-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic implications of 2018 guideline for the diagnosis of idiopathic pulmonary fibrosis in clinical practice

Abstract: The purpose of this study was to evaluate the implications of the 2018 updated guideline for the diagnosis of idiopathic pulmonary fibrosis (IPF) in clinical practice compared to 2011 guideline. This study involved 535 patients including 339 IPF and 196 non-IPF, and we retrospectively evaluated CT classifications of usual interstitial pneumonia (UIP) by two guidelines. Interobserver agreement of 2018 criteria showed moderate reliability (κ = 0.53) comparable to 2011 (κ = 0.56) but interobserver agreement for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In our study, there were cases in which both IR and DLM were suggestive of such results (Figs 2 and 3 ). Another possible reason for the discrepant diagnoses is that the reported interobserver agreement in diagnosing UIP pattern is not high ranging 0.40–0.69 [ 3 , 6 , 34 ]. The diagnostic agreement between the two radiologists in this study was substantial; however, variability may have influenced the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there were cases in which both IR and DLM were suggestive of such results (Figs 2 and 3 ). Another possible reason for the discrepant diagnoses is that the reported interobserver agreement in diagnosing UIP pattern is not high ranging 0.40–0.69 [ 3 , 6 , 34 ]. The diagnostic agreement between the two radiologists in this study was substantial; however, variability may have influenced the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the guidelines related to IPF, lymphocyte counts in the BALF of patients with IPF are lower than those in patients with non-IPF interstitial pneumonia [22]. Takei et al reported that the differential lymphocyte count in the BALF was a prognostic factor for acute exacerbation in patients with chronic fibrosing IIPs [23].…”
Section: Plos Onementioning
confidence: 99%